Konteks Analisis Masyarakat Mengenai Pemilihan Brand ambasador Produk Ms. Glow - Riyantie, Mayang; Ariyani, Nafiah; Soraya, Haniifah (Universitas Prof. Dr. Moestopo (Beragama), 2024)
The purpose of this research is to understand the public's perspective on MS.Glow skincare with Brand Ambassadors Marshel Widianto and Babe Cabita, as well as to identify the supporting and inhibiting factors of Ms.Glow's Brand Ambassadors Marshel Widianto and Babe Cabita in promoting Ms.Glow products. This study utilizes a qualitative research method involving interviews, observations, and documentation. Data validity is ensured through triangulation of sources, and data analysis is conducted through stages of reduction, presentation, and conclusion. The research findings reveal that 10 key informants from the public view MS.Glow's actions as an innovation, setting it apart from other skincare manufacturers. The supporting factors include novel approaches and uniqueness, enhancing MS.Glow's sales. However, the inhibiting factor stems from the Brand Ambassadors, deviating from the typical skincare brand ambassador image and causing controversy among the public. In conclusion, this study illustrates that MS.Glow has successfully introduced innovations in skincare, distinguishing the brand from its competitors. These innovations stem from a fresh approach within the skincare industry, creating a positive impression on consumers and boosting sales. However, the utilization of Brand Ambassadors by MS.Glow has elicited negative reactions from the public due to misalignment with consumer expectations and industry conventions.